Legal Regulation of the Caretaker Government In the Kurdistan Region – Iraq - Ahmed, Ramadhan (Humanities Journal of University of Zakho, 2021)
The caretaker government that is applied at the state level was found as a temporary solution for the perpetuation of the vital public institutions until the formation of a legitimate government according to legal foundations, and because there is no constitution or law in the Kurdistan Region that treat the legal status of the caretaker government and defines its powers, and because there are no constitutional or legal rules obligating political parties In the region with a specific time limit as a maximum for the formation of the government, all of this prompted us to say that standing on the legal regulation of the caretaker government in the Kurdistan region is one of the issues worthy of research and we discussed in it what is the caretaker government in light of the principles of the parliamentary system followed in the Kurdistan region, and we touched upon Diagnosing the legislation that regulating the work of the legislative and executive authorities in the region. We discussed the texts that dealt with cases of resignation, the dissolution of parliament and the expiry of the term of the Council of Ministers. We showed whether the Kurdistan legislator used the term caretaker government or any other designation to express the transformation of the government into a government with lacking powers, as well as We discussed the cases of their application and the content of the works that fall within the ordinary matters, and we also showed the extent of the Kurdistan legislator’s commitment to The parliamentary system was established in regulating the work of the Council of Ministers (the government) and Parliament, and to what extent the Kurdistan legislature was successful in dealing with the issue of the caretaker government.